Storybird-Based Narrative Writing Activities among Indonesian EFL Learners: Focusing on Contributions - Fuad Abdullah; Soni Tantan Tandiana; Risma Amelia (Premise: Journal of English Education and Applied Linguistics, 2020)
The advancement of Information, Communication and Technology (ICT) has significantly affected English language teaching, such as the utilization of miscellaneous applications, social media and other digital platforms facilitating the learners to invigorate their language skills, notably L2/FL writing context. However, insufficient attention has been addressed to the contributions of employing storybird to the learners’ narrative writing activities. To fill this void, this study aimed at delineating the contributions of employing storybird to the Indonesian EFL learners’ narrative writing activities. Three Indonesian junior high school learners participated as research participants. The data were gathered through semi-structured interview and analyzed with Thematic Analysis (Braun & Clarke, 2006). The findings designated that storybird (1) generated ideas for writing a story (2) facilitated to construct generic structure of English narrative texts (3) considered lexicogrammatical features of English narrative texts (4) produced English narrative texts joyfully and (5) wrote English narrative texts actively. Given these facts, storybird enables the learners to think creatively, provides them enjoyable learning experiences, brings their abstract thoughts to real life and guide them to communicate and collaborate effectively.